2022
DOI: 10.1371/journal.pone.0273290
|View full text |Cite|
|
Sign up to set email alerts
|

mHealth intervention to improve quality of life in patients with chronic diseases during the COVID-19 crisis in Paraguay: A study protocol for a randomized controlled trial

Abstract: Background Patients with chronic disease represent an at-risk group in the face of the COVID-19 crisis as they need to regularly monitor their lifestyle and emotional management. Coping with the illness becomes a challenge due to supply problems and lack of access to health care facilities. It is expected these limitations, along with lockdown and social distancing measures, have affected the routine disease management of these patients, being more pronounced in low- and middle-income countries with a flawed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Participants were excluded if they met any exclusion criteria: (1) in the acute stage of disease, or severe cardiopulmonary, renal insufficiency, or terminal disease stage; (2) with communication, cognitive, or mental disorders; (3) being participating in other research. Previous studies reported chronic diseases situation among older adults people in communities is relatively complex, many people have multiple types of chronic diseases, and the severity of different chronic diseases varies ( 19 ). Therefore, this study did not distinguish disease types or severity.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were excluded if they met any exclusion criteria: (1) in the acute stage of disease, or severe cardiopulmonary, renal insufficiency, or terminal disease stage; (2) with communication, cognitive, or mental disorders; (3) being participating in other research. Previous studies reported chronic diseases situation among older adults people in communities is relatively complex, many people have multiple types of chronic diseases, and the severity of different chronic diseases varies ( 19 ). Therefore, this study did not distinguish disease types or severity.…”
Section: Methodsmentioning
confidence: 99%